Business Development at Amplispot Technologies - Lord, Meher Aspi (ATLAS SkillTech University, 2024)
As a second-year MBA student at ATLAS SkillTech University, my internship experience at Amplispot Technologies over the course of three months was a transformative journey into the world of business development and technology solutions. Amplispot Technologies, a dynamic and innovative company specializing in tech-driven solutions, provided me with a rich learning experience and exposed me to the intricacies of the business world.
Project Report on Business Development at Amplispot Technologies (2022-24) Under the Guidance of Prof. Tapish Panwar
Keywords: Amplispot; Technologies; Business Development